Is the effect of disaggregated public spending on unemployment reinforced by governance in Cameroon? - Patrick, Dzou Pierre; Gilbert, Noula Armand; Gerard, Tchouassi; Orfe, Chouafi Nguekam; Salim, Ngnemadon Ahmed Ali (Asian Journal of Empirical Research, 2023)
In this article, we sought to examine the effect of Cameroon’s public expenditure, with a focus on governance, on the reduction of unemployment from 1988 to 2020. By implementing a multiple linear regression model and applying the OLS method, we found that only military spending significantly contributed to the decrease in youth unemployment. Nonetheless, the efficacy of all types of public expenditure is heavily contingent upon socio-economic conditions. It is apparent that corruption and economic crises contribute greatly to the unemployment rate, hence why public entities must make greater efforts to form a strict institutional framework governing the labor market and invest in anti-exogenous shock programs. This would ensure that unemployment rates can be decreased systematically and substantially.